KARAKTERISTIK AKSARA PAKPAK BERDASARKAN SUMBER TERTULIS DI DAIRI DAN PAKPAK BHARAT, SUMATERA UTARA - Nasoichah, Churmatin; Tedjowasono, Ninny Soesanti; Sibarani, Tomson; Sekali, Mehammat Br. Karo; Andhifani, Wahyu Rizky; Lumban Tobing, Lolita Refani (UI Scholars Hub, 2023)
The Pakpak ethnic group occupy two areas in North Sumatra, namely Dairi and Pakpak Bharat, and speak a language with its own set of characters called the Pakpak script. This study discusses the Pakpak script characteristics and writing materials, and provides a compiled description of the Pakpak community in the past based on written sources. The purpose of this study is to determine the characteristics of the Pakpak script and provide a historical description of the ethnic group based on written sources. This study uses the exploratory inductive reasoning model. Results show that the Pakpak and Batak scripts share similar characteristics. Stones and tree barks were the two main media on which the script was written. Based on historical records, the Pakpak people practiced animism with a unique burial system in which corpses were burned and the ashes were then placed in stone grave containers called perabuen. The livelihood system of the Pakpak community was dominated by rice farming. There was also a social system consisting of permangmang (the “oldest” clan) and persinabul(the “younger” clan), each of which had to respect each other and obey the existing rules.